High-performance high-resistivity neodymium-iron-boron magnet and method for producing same

CN122907459APending Publication Date: 2026-10-13JINLI PERMANENT MAGNET (GANZHOU) NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610788384.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

1、采用掺杂高电阻率化合物(如CaF2、AlN、ZrN等)或制备复合绝缘层等方法,然而,这些方法往往存在明显缺陷,例如,CaF2掺杂对电阻率的提升效果有限,还会导致磁性能(如剩磁、矫顽力)的大幅衰减,而AlN、ZrN等掺杂虽能显著提高电阻率,但会导致磁性能(如剩磁、矫顽力)的急剧衰减;

Benefits of technology

[0016]在本发明内,通过晶界扩散引入氟、氧非金属元素,在晶界处形成高电阻率相,有效阻碍电子传输,从而提高钕铁硼磁体的电阻率;而且,通过优化扩散源成分和工艺参数,将磁性能的损失控制在较低水平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907459A_ABST
    Figure CN122907459A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of rare earth permanent magnet materials, and particularly relates to a high-performance high-resistivity neodymium-iron-boron magnet and a preparation method thereof; the present application comprises a magnet comprising a grain boundary diffusion layer, which is formed after coating a diffusion source; in the present application, fluorine and oxygen non-metal elements are introduced through grain boundary diffusion to form a high-resistivity phase at the grain boundary, which effectively hinders electron transmission, thereby improving the resistivity of the neodymium-iron-boron magnet; moreover, by optimizing the composition of the diffusion source and the process parameters, the loss of magnetic properties is controlled at a low level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rare earth permanent magnet materials technology, and in particular to a high-performance, high-resistivity neodymium iron boron magnet and its preparation method. Background Technology

[0002] Sintered neodymium iron boron (Nd-Fe-B) permanent magnet materials are widely used in motors, sensors, power equipment and other fields due to their extremely high magnetic energy product. They are especially dominant in high-performance applications such as drive motors for new energy vehicles and high-speed permanent magnet motors. However, the resistivity of traditional sintered neodymium iron boron magnets is low (usually below 150 μΩ•cm), which will generate significant eddy current losses under high-frequency or high-speed conditions, leading to magnet heating, reduced efficiency, and even thermal demagnetization, which seriously restricts their application in high-end motors.

[0003] To improve resistivity, existing technologies mainly employ the following methods: 1. Methods such as doping with high resistivity compounds (e.g., CaF2, AlN, ZrN) or preparing composite insulating layers are employed. However, these methods often have significant drawbacks. For example, CaF2 doping has a limited effect on improving resistivity and can lead to a significant decrease in magnetic properties (e.g., remanence and coercivity). While doping with AlN and ZrN can significantly improve resistivity, it can also lead to a sharp decrease in magnetic properties (e.g., remanence and coercivity). 2. Resistivity can be improved by constructing a layered structure of inorganic materials, but this process is complex, costly, and difficult to industrialize.

[0004] Therefore, how to effectively improve the resistivity of sintered NdFeB while maintaining its inherent excellent magnetic properties to the greatest extent has become a key technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To overcome the above shortcomings, the present invention aims to provide a high-performance, high-resistivity neodymium iron boron magnet, and also provides a method for preparing a high-performance, high-resistivity neodymium iron boron magnet. The method employs grain boundary diffusion technology to introduce non-metallic elements from the diffusion source into the grain boundaries of the magnet, thereby significantly improving the individual resistivity of the material while minimizing the negative impact on magnetic properties.

[0006] The technical solution of this invention to solve its technical problem is: A high-performance, high-resistivity neodymium iron boron magnet includes a magnet comprising a grain boundary diffusion layer, wherein the grain boundary diffusion layer is formed after coating with a diffusion source, and the diffusion source is RH. i X (1-i)The mixture consists of three elements: ReF and ReO. RH is one or two of Dy and Tb, X is one or more of Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, Mo, Ni, and Fe, with 10wt%≤i≤100wt%; Re is one or more of Pr, Nd, Y, Ce, La, and Gd; F is fluorine; and O is oxygen.

[0007] As an improvement of the present invention, within the diffusion source, 80wt%≤RH i X (1-i) ≤97wt%, 2wt%<ReF≤15wt%, 1wt%≤ReO≤5wt%.

[0008] As a further improvement of the present invention, the magnet is R x -M y -B z -T (1-x-y-z) The structural formula is as follows: R is one or more rare earth elements Pr, Nd, Dy, Tb, Ho, and Gd; M is one or more rare earth elements Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, and Mo; B is boron; and T is Fe and Co. The formula is as follows: 28wt%≤x≤34wt%, 0<y≤3wt%, and 0.85wt%≤z≤1wt%.

[0009] A method for preparing a high-performance, high-resistivity neodymium iron boron magnet, comprising the following steps: Step S1: Add each element raw material according to the above composition ratio of the magnet, then melt it to make a cast alloy, and then obtain a block substrate after powdering, molding and sintering. Then process the block substrate to cut it into sheet substrate. Step S2: Add an organic solvent to the diffusion source to prepare a diffusion source slurry; Step S3: Coat the diffusion source slurry onto the orientation surface of the sheet substrate to obtain a semi-finished product; Step S4: After performing diffusion heat treatment on the semi-finished product obtained in step S3, neodymium iron boron magnets are obtained.

[0010] As a further improvement of the present invention, in step S1, the particle size of the alloy powder obtained in the powder preparation is 3um to 5um.

[0011] As a further improvement of the present invention, in step S2, the particle size of the alloy powder of the diffusion source is 1 μm to 3 μm.

[0012] As a further improvement of the present invention, in step S2, the organic solvent includes one or more of gasoline, ethanol and acrylic acid.

[0013] As a further improvement of the present invention, in step S3, the coating method is one of spraying, dipping or printing.

[0014] As a further improvement of the present invention, in step S4, the heat treatment includes low-temperature diffusion treatment and tempering diffusion treatment.

[0015] As a further improvement of the present invention, the diffusion treatment temperature is 800℃~950℃ and the diffusion treatment time is 4h~24h; the tempering diffusion treatment temperature is 450℃~600℃ and the tempering diffusion treatment time is 2h~12h.

[0016] In this invention, fluorine and oxygen nonmetallic elements are introduced through grain boundary diffusion to form a high resistivity phase at the grain boundary, which effectively hinders electron transport and thus improves the resistivity of the NdFeB magnet. Moreover, by optimizing the composition of the diffusion source and process parameters, the loss of magnetic properties is controlled to a low level. Attached Figure Description

[0017] For ease of explanation, the present invention will be described in detail below with reference to the preferred embodiments and accompanying drawings.

[0018] Figure 1 A comparison graph showing the magnetic properties and resistivity in the 40mm direction of different embodiments of the present invention; Figure 2 This is a comparison chart of magnetic performance parameters and resistivity in the 40mm direction for different embodiments of the present invention. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0020] like Figure 1 and Figure 2 As shown, the present invention discloses a high-performance, high-resistivity neodymium iron boron magnet, comprising a magnet containing a grain boundary diffusion layer, wherein the grain boundary diffusion layer is formed after coating with a diffusion source, and the diffusion source is RH. i X (1-i) The mixture consists of three elements: ReF and ReO. RH is one or both of Dy and Tb; X is one or more of Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, Mo, Ni, and Fe, with 10wt% ≤ i ≤ 100wt%; Re is one or more of Pr, Nd, Y, Ce, La, and Gd; F is fluorine; and O is oxygen. Within the diffusion source, 80wt% ≤ RH. i X (1-i)≤97wt%, 2wt%<ReF≤15wt%, 1wt%≤ReO≤5wt%.

[0021] Within this invention, the magnet is R. x -M y -B z -T (1-x-y-z) The structural formula is as follows: R is one or more rare earth elements Pr, Nd, Dy, Tb, Ho, and Gd; M is one or more rare earth elements Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, and Mo; B is boron; and T is Fe and Co. The formula is as follows: 28wt%≤x≤34wt%, 0<y≤3wt%, and 0.85wt%≤z≤1wt%.

[0022] This invention provides a method for preparing a high-performance, high-resistivity neodymium iron boron magnet, comprising the following steps: Step S1, according to magnet R x -M y -B z -T (1-x-y-z) The raw materials are added according to the composition ratio, and then smelted to make cast sheet alloy. After powdering, molding and sintering, block substrate is obtained. The block substrate is then processed to cut into sheet substrate. Step S2: Add an organic solvent to the diffusion source to prepare a diffusion source slurry; Step S3: Coat the diffusion source slurry onto the orientation surface of the sheet substrate to obtain a semi-finished product; Step S4: After performing diffusion heat treatment on the semi-finished product obtained in step S3, neodymium iron boron magnets are obtained.

[0023] In step S1, the particle size of the alloy powder obtained in the powder preparation is 3um to 5um. In step S2, the particle size of the alloy powder of the diffusion source is 1um to 3um. The organic solvent includes one or more of gasoline, ethanol and acrylic acid.

[0024] In this invention, in step S3, the coating method is one of spraying, dipping, or printing.

[0025] In this invention, in step S4, the heat treatment includes low-temperature diffusion treatment and tempering diffusion treatment. The diffusion treatment temperature is 800℃~950℃ and the diffusion treatment time is 4h~24h; the tempering diffusion treatment temperature is 450℃~600℃ and the tempering diffusion treatment time is 2h~12h.

[0026] The present invention provides the following embodiments and comparative examples:

[0027] Example 1

[0028] (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 92wt% Dy 95 (CuAlFe)5 alloy powder, 4wt% NdF3 and 4wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 1 .

[0029] Comparative Example 1 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 100wt% Dy 95 (CuAlFe)5 alloy powder is added to an organic solvent to prepare a diffusion source slurry. The diffusion slurry is then uniformly coated on the two largest surfaces of the substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 1 .

[0030] Comparative Example 2 (1) According to R x -M y -B z -T (1-x-y-z)The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 92wt% Dy 95 (CuAlFe)5 alloy powder and 8wt% NdF3 were added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry was uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 1 .

[0031] Comparative Example 3 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 92wt% Dy 95 (CuAlFe)5 alloy powder and 8wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 1 .

[0032] Through such Figure 1 As shown in Example 1 and Comparative Examples 1-3, it can be seen that by introducing fluorine and oxygen nonmetallic elements through grain boundary diffusion, a high resistivity phase is formed at the grain boundaries, effectively hindering electron transport. This can increase the resistivity of sintered NdFeB magnets from the conventional 130 μΩ·cm to 150 μΩ·cm, and up to a maximum of 170 μΩ·cm, representing a maximum increase of over 30%. Therefore, from Figure 1 A comparison of the data from Example 1 and Comparative Examples 1, 2, and 3 shows that the addition of fluorides and oxides results in a more significant increase in resistivity.

[0033] Example 2

[0034] (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 93wt% Dy 95 (AlNiFe)5 alloy powder, 5wt% PrF3 and 2wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0035] Comparative Example 4 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 93wt% Dy 95 (AlNiFe)5 alloy powder, 6.5wt% PrF3 and 0.5wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0036] Comparative Example 5 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 93wt% Dy 95 (AlNiFe)5 alloy powder, 2wt% PrF3 and 5wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0037] Comparative Example 6 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 93wt% Dy 95 (AlNiFe)5 alloy powder, 1wt% PrF3 and 6wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0038] Example 3

[0039] (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 83wt% Dy 95 (AlNiFe)5 alloy powder, 14wt% PrF3 and 3wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0040] Comparative Example 7 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 83wt% Dy 95 (AlNiFe)5 alloy powder, 11wt% PrF3 and 6wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0041] Comparative Example 8 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 83wt% Dy 95 (AlNiFe)5 alloy powder, 16wt% PrF3 and 1wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0042] Comparative Example 9 (1) According to R x -M y -B z -T (1-x-y-z) The raw materials of each element are added in the following proportions: R is 31% by mass, M is 0.95% by mass, B is 0.92% by mass, and T is 67.13% by mass. After being melted, it is made into a cast alloy. Then, after being powdered, shaped and sintered, a NdFeB 45SH block blank is obtained. It is then machined into a sheet matrix of 40*30*3.1mm and cleaned by ultrasonic degreasing. (2) According to 83wt% Dy 95 (AlNiFe)5 alloy powder, 16.5wt% PrF3 and 0.5wt% (PrNd)2O3 are added to an organic solvent to prepare a diffusion source slurry. The above diffusion slurry is uniformly coated on the two largest surfaces of the above substrate at a mass ratio of 1.0% Dy to obtain a semi-finished product. (3) After the semi-finished product obtained in the above steps is subjected to diffusion heat treatment, a rare earth permanent magnet is obtained; (4) The above-mentioned diffused magnets are machined into finished magnets of 40*30*3.0mm. The properties of the diffused magnets are shown in [reference needed]. Figure 2 .

[0043] like Figure 2As shown, a comparison of the data from Example 2 and Comparative Examples 4, 5, and 6, as well as the data from Example 3 and Comparative Examples 7, 8, and 9, reveals that when fluorides and oxides are added in combination, the ratio of fluorides to oxides must be within a specific range for a more significant increase in resistivity. Furthermore, fluorides provide a more significant increase in resistivity than oxides, but their overall performance degrades considerably.

[0044] While improving resistivity, this invention optimizes the composition of the diffusion source and process parameters to keep the loss of magnetic properties at a low level. Typically, the reduction in remanence (Br) of the treated magnet can be kept within 0.02T, the reduction in coercivity (Hcj) can be kept within 0.5 kOe, the maximum energy product ((BH)max) reaches more than 320 kJ / m³, and the overall magnetic property attenuation is less than 5%.

[0045] The present invention has the following advantages: 1. Significantly improve resistivity: By introducing non-metallic elements such as fluorine and oxygen through grain boundary diffusion, a high resistivity phase is formed at the grain boundary, which effectively hinders electron transport. This can increase the resistivity of sintered NdFeB magnets from the conventional 130μΩ•cm to more than 150μΩ•cm, and up to about 170μΩ•cm, an increase of more than 30%.

[0046] 2. Excellent magnetic performance retention: While achieving a significant increase in resistivity, the loss of magnetic performance is controlled at a low level by optimizing the composition of the diffusion source and process parameters. The remanence (Br) of the treated magnet can be maintained above 1.3T, the coercivity (Hcj) exceeds 800 kA / m, the maximum magnetic energy product ((BH)max) reaches more than 320kJ / m³, and the overall magnetic performance attenuation is less than 10%.

[0047] 3. Broad application prospects: The high resistivity neodymium iron boron magnets prepared are particularly suitable for high-frequency and high-speed motors that are sensitive to eddy current losses, such as new energy vehicle drive motors, wind turbines, and precision servo motors. They can significantly reduce motor temperature rise and improve efficiency and operational reliability.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-performance, high-resistivity neodymium iron boron magnet, characterized in that, This includes a magnet containing a grain boundary diffusion layer, which is formed after coating a diffusion source, wherein the diffusion source is RH. i X (1-i) The mixture consists of three elements: ReF and ReO. RH is one or two of Dy and Tb, X is one or more of Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, Mo, Ni, and Fe, with 10wt%≤i≤100wt%; Re is one or more of Pr, Nd, Y, Ce, La, and Gd; F is fluorine; and O is oxygen.

2. The high-performance, high-resistivity neodymium iron boron magnet according to claim 1, characterized in that, Within the diffusion source, 80wt%≤RH i X (1-i) ≤97wt%, 2wt%<ReF≤15wt%, 1wt%≤ReO≤5wt%.

3. A high-performance, high-resistivity neodymium iron boron magnet according to claim 1 or 2, characterized in that, The magnet is R x -M y -B z -T (1-x-y-z) The structural formula is as follows: R is one or more rare earth elements Pr, Nd, Dy, Tb, Ho, and Gd; M is one or more rare earth elements Cu, Al, Cr, Nb, Zr, Ga, Ti, Mn, Zn, V, and Mo; B is boron; and T is Fe and Co. The formula is as follows: 28wt%≤x≤34wt%, 0<y≤3wt%, and 0.85wt%≤z≤1wt%.

4. A method for preparing a high-performance, high-resistivity neodymium iron boron magnet, characterized in that, Includes the following steps: Step S1: Add each element raw material according to the composition ratio of the magnet described in claim 3, then melt it to make a cast alloy, and then obtain a block substrate after powdering, molding and sintering. Then process the block substrate to cut it into sheet substrates. Step S2: Add an organic solvent to the diffusion source to prepare a diffusion source slurry; Step S3: Coat the diffusion source slurry onto the orientation surface of the sheet substrate to obtain a semi-finished product; Step S4: After performing diffusion heat treatment on the semi-finished product obtained in step S3, neodymium iron boron magnets are obtained.

5. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 4, characterized in that, In step S1, the particle size of the alloy powder obtained in the powder preparation is 3µm to 5µm.

6. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 4, characterized in that, In step S2, the particle size of the alloy powder of the diffusion source is 1 μm to 3 μm.

7. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 4, characterized in that, In step S2, the organic solvent includes one or more of gasoline, ethanol, and acrylic acid.

8. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 4, characterized in that, In step S3, the coating method is one of spraying, dipping, or printing.

9. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 4, characterized in that, In step S4, the heat treatment includes low-temperature diffusion treatment and tempering diffusion treatment.

10. The method for preparing a high-performance, high-resistivity neodymium iron boron magnet according to claim 9, characterized in that, The diffusion treatment temperature is 800℃~950℃, and the diffusion treatment time is 4h~24h; the tempering diffusion treatment temperature is 450℃~600℃, and the tempering diffusion treatment time is 2h~12h.